2013
DOI: 10.1088/0004-637x/766/2/75
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variations of X-Ray Solar Flare Loops: Length, Corpulence, Position, Temperature, Plasma Pressure, and Spectra

Abstract: The spatial and spectral properties of three solar flare coronal X-ray loops are studied before, during and after the peak X-ray emission. Using observations from the Ramaty High Energy Solar Spectroscopic Imager (RHESSI), we deduce the temporal changes in emitting X-ray length, corpulence, volume, position, number density and thermal pressure. We observe a decrease in the loop length, width and volume before the X-ray peak, and an increasing number density and thermal pressure. After the X-ray peak, volume in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 46 publications
0
20
0
1
Order By: Relevance
“…The apparent radius of the loop (the radius of the emitting plasma) varies as a function of time in our simulations (cf. Jeffrey & Kontar 2013). The width of the emitting region is initially smaller than that of the actual magnetic flux-rope, but increases quickly as the instability proceeds.…”
Section: Thermal X-ray Emissionmentioning
confidence: 96%
See 1 more Smart Citation
“…The apparent radius of the loop (the radius of the emitting plasma) varies as a function of time in our simulations (cf. Jeffrey & Kontar 2013). The width of the emitting region is initially smaller than that of the actual magnetic flux-rope, but increases quickly as the instability proceeds.…”
Section: Thermal X-ray Emissionmentioning
confidence: 96%
“…If our model had represented a real solar flare, these details would only be detectable as a fast initial increase in thickness and length of the flaring coronal loop (cf. Jeffrey & Kontar 2013), given the spatial resolution of the current X-ray instruments. Interestingly, the initial magnetic twist in the pre-flare flux-rope as perceived from the X-ray emission is much weaker than the highest twist at these instants.…”
Section: Comparison With Sxr Observationsmentioning
confidence: 99%
“…The forcing terms manifest as terms in the momentum and energy equations. The flux tubes are constructed to match observed models (e.g., Verth et al 2011;Jeffrey & Kontar 2013) and stable multiple flux tubes are regularly observed in pressure equilibrium (e.g., Levine & Withbroe 1977;McGuire et al 1977;Malherbe et al 1983). Perturbations in such stable flux tubes are investigated in a large number of observational, numerical, and theoretical studies (see, for example, reviews cited in the Introduction).…”
Section: Numerical Configurationmentioning
confidence: 99%
“…Svestka et al 1987;Tsuneta et al 1992;Švestka 1996;Gallagher et al 2002). Sometimes an initial decrease in altitude is followed by an increase in altitude after the impulsive phase of the flare (Sui & Holman 2003;Sui et al 2004;Veronig et al 2006;Liu et al 2009;Joshi et al 2009;Reznikova et al 2010;Gosain 2012;Jeffrey & Kontar 2013), and sometimes even more complicated motions are observed (e.g. Liu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Sub-arcsecond measurements of X-ray footpoint locations have been achieved using X-ray visibilities (see e.g. Kontar et al 2008Kontar et al , 2010Jeffrey & Kontar 2013), improving upon forward fitting a Gaussian source model to the RHESSI modulated lightcurves (e.g. Aschwanden et al 2002).…”
Section: Introductionmentioning
confidence: 99%